Case Report: Rare cardiovascular characteristics of tuberous sclerosis complex with novel TSC2 variant - Zhiqin Du; Xiao Ma; Xiao Ma; Xiao Ma; Jianhua Li; Fang Yang; Yangfan Guo; Yangfan Guo (Frontiers in Cardiovascular Medicine)
BackgroundTuberous sclerosis complex (TSC) is a multisystem genetic disorder primarily characterized by the development of benign tumors in multiple organs. While cardiovascular involvement is less common than neurological or renal manifestations, it typically presents with cardiac rhabdomyomas (CRs). The co-occurrence of a bicuspid aortic valve (BAV) with TSC is exceedingly rare.Case summaryWe report the case of a 26-year-old woman with genetically confirmed TSC, harboring a novel pathogenic variant in the TSC2 gene. Cardiovascular characteristics included a history of heart valve disease, a bicuspid aortic valve, and severe aortic regurgitation. multi-system characteristics of TSC were also presented, affecting skin, brain, lung, kidney, and bone. She underwent aortic valve replacement but experienced postoperative complications, including significant pleural and pericardial effusions requiring drainage and subsequent thoracic duct ligation.ConclusionThis case expands the clinical spectrum of TSC-associated cardiovascular abnormalities, highlighting the rare association of BAV with this disorder. Our finding emphasizes the importance of considering TSC in individuals presenting with these cardiac features, as well reinforce the critical role of molecular genetic testing in confirming the diagnosis of TSC.